PODER E NEGOCIAÇÃO DE IDENTIDADES EM REUNIÕES ACADÊMICAS - Brandão, Cibele (Cadernos de Linguagem e Sociedade, 2010)
This paper is concerned about an analysis of power relations constituted by academic members in micro-interactions, as well as in the practice of identities negotiation that emerge from these interactions. The analysis shows how identities are constructed when academics establish power relations in the institutional setting of academic meetings. Power is observed in relation to asymmetric discourse, resistant discourse and in the struggle for the control of turns and agenda.